2014
DOI: 10.5194/hess-18-2049-2014
|View full text |Cite
|
Sign up to set email alerts
|

Improving the complementary methods to estimate evapotranspiration under diverse climatic and physical conditions

Abstract: Abstract. Reliable estimation of evapotranspiration (ET) is important for the purpose of water resources planning and management. Complementary methods, including complementary relationship areal evapotranspiration (CRAE), advection aridity (AA) and Granger and Gray (GG), have been used to estimate ET because these methods are simple and practical in estimating regional ET using meteorological data only. However, prior studies have found limitations in these methods especially in contrasting climates. This stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…However no similar observations were found for the GG model (Han et al, 2011;Xu and Chen, 2005). Recently, Anayah and Kaluarachchi (2014) reported that the GG model was the most attractive when compared to the CRAE and AA models across 34 global sites. In our prior evaluation studies, the performance of the GG model was quite satisfactory among five commonly used ET models (see details in Supplement 1).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…However no similar observations were found for the GG model (Han et al, 2011;Xu and Chen, 2005). Recently, Anayah and Kaluarachchi (2014) reported that the GG model was the most attractive when compared to the CRAE and AA models across 34 global sites. In our prior evaluation studies, the performance of the GG model was quite satisfactory among five commonly used ET models (see details in Supplement 1).…”
Section: Introductionmentioning
confidence: 61%
“…Thus, its applicability over a wide range of land types and climatic conditions need to be further investigated (Long and Singh, 2010). Secondly, the GG model has mostly been used on a specific timescale, namely monthly (Xu and Singh, 2005;Anayah and Kaluarachchi, 2014), daily (Han et al, 2011) and subdiurnal (Crago and Crowley, 2005). However, systematic comparisons of its performances on different timescales are relatively sparse and its dependence on timescales is not fully understood (Crago and Qualls, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The complementary principle, first proposed by Bouchet (1963), has provided a convenience for estimating terrestrial ET from meteorological observations only (e.g., Anayah & Kaluarachchi, 2014;Granger & Gray, 1989;Han & Tian, 2018;Kahler & Brutsaert, 2006;Morton, 1983;Szilagyi et al, 2017). This framework includes three ET definitions, namely, the actual ET (ET a ), the wet environment ET (ET w ), and the potential ET (ET p ).…”
Section: Generalized Complementary Principlementioning
confidence: 99%
“…Estimating normalE in equation is key to calculate SWI. There are several methods for estimating normalE, such as remote sensing [ Mu et al ., ] and Bouchet hypothesis (AA or GG model) [ Anayah and Kaluarachchi , ]. Here we use the Budyko framework [ Budyko , ; Wang and Tang , ; Zhou et al ., ], one of the most widely used equations, as follows [ Choudhury , ]: normalE=normalP·ET0normalPnormaln+normalEnormalT0normaln1/n where normaln represents the joint effects of climate and land surface [ Berghuijs and Woods , ].…”
Section: Development Of the Standardized Wetness Index (Swi)mentioning
confidence: 99%